2023
DOI: 10.3390/molecules28083510
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of New Green Propolis Extract Formulations as Promising Candidates to Substitute for Green Propolis Hydroalcoholic Extract

Abstract: The technologies used to produce the different dosage forms of propolis can selectively affect the original propolis compounds and their biological activities. The most common type of propolis extract is hydroethanolic. However, there is considerable demand for ethanol-free propolis presentations, including stable powder forms. Three propolis extract formulations were developed and investigated for chemical composition and antioxidant and antimicrobial activity: polar propolis fraction (PPF), soluble propolis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 52 publications
(85 reference statements)
3
1
0
Order By: Relevance
“…Propolis EPP-AF ® microcapsules were obtained by dispersion of an alcoholic extract of propolis in aqueous solution containing gum arabic (40:60, propolis and gum arabic). The emulsion preparation conditions, including the proportions of the dry mass of propolis and gum arabic, were previously published by Berretta et al [7]. The ratio of propolis: gum arabic (40:60) resulted in approximately 40% propolis w/w in microcapsules (EPP-AF ® i-CAPs).…”
Section: Propolis Epp-af ® and Epp-af ® Microencapsulated Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Propolis EPP-AF ® microcapsules were obtained by dispersion of an alcoholic extract of propolis in aqueous solution containing gum arabic (40:60, propolis and gum arabic). The emulsion preparation conditions, including the proportions of the dry mass of propolis and gum arabic, were previously published by Berretta et al [7]. The ratio of propolis: gum arabic (40:60) resulted in approximately 40% propolis w/w in microcapsules (EPP-AF ® i-CAPs).…”
Section: Propolis Epp-af ® and Epp-af ® Microencapsulated Extractsmentioning
confidence: 99%
“…The process included dispersing gum arabic in purified water and then, with agitation, dispersing the hydroethanolic extract, resulting in an emulsion. The emulsion was dried with a spray-drying system (Labmaq MSD 1.0, Ribeirão Preto, Brazil), using the equipment conditions defined by Berretta et al [7]. Detailed composition and process are available in Berretta et al [7].…”
Section: Propolis Epp-af ® and Epp-af ® Microencapsulated Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the promising antioxidant activity of propolis through the mechanisms of elimination, neutralization, and the removal of reactive species after the induction of oxidative stress, and by preventing lipid peroxidation [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Propolis serves essential functions within the hive and has garnered attention for its potential health benefits in human use. Its rich and varied chemical composition makes it a subject of ongoing scientific inquiry and a valuable resource in traditional and modern medicine [9][10][11][12]. Due to its possible therapeutic characteristics, propolis has been exploited for various objectives, including immunity-enhancing, anti-inflammatory, antihypertensive, antimicrobial, antioxidant, antiulcer, and antitumor activities [13][14][15].…”
Section: Introductionmentioning
confidence: 99%